2018
DOI: 10.1016/j.jmatprotec.2017.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SLM process parameters on the surface finish, porosity rate and fatigue behavior of as-built Inconel 625 parts

Abstract: This paper is dedicated to understanding fatigue crack initiation for an Inconel 625 manufactured by SLM, using a hatching + contour procedure. In the first part of the paper, an optimum set of parameters was found to deliver the best surface roughness combined with low porosity. This process optimization, mostly focused on adjusting the volume energy density aimed at finding a compromise between an optimum densification state and a minimum number of contaminating spatters. Secondly, a fatigue test campaign ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(130 citation statements)
references
References 22 publications
6
111
0
Order By: Relevance
“…Forthcoming experiments were conducted based on this parameter set, as it appears to be promising for the fabrication of nearly defect-free specimens made of case-hardening steel 16MnCr5. This is important, as internal defects can act as crack initiators, as it was already shown for different metallic materials in [18,19].…”
Section: Identification Of Suitable Parameter Rangementioning
confidence: 81%
“…Forthcoming experiments were conducted based on this parameter set, as it appears to be promising for the fabrication of nearly defect-free specimens made of case-hardening steel 16MnCr5. This is important, as internal defects can act as crack initiators, as it was already shown for different metallic materials in [18,19].…”
Section: Identification Of Suitable Parameter Rangementioning
confidence: 81%
“…The contour scans are usually applied to reduce roughness of the sample, which is often dominated by the attached/partially unmolten powder particles [34]. However, in order to understand the effect of roughness on RS measurements one A4 sample without contour was investigated in this study.…”
Section: Effect Of Surface Roughnessmentioning
confidence: 99%
“…Cherry et al investigated the relationship between the laser energy density and the properties of 316 L stainless steel [8], such as its porosity, surface roughness, microstructure, density and hardness. Koutiri et al focused on adjusting the volume energy density with the goal of finding a compromise between an optimum densification state and a minimum amount of contaminating spatter [9], and they finally found an optimum set of parameters that delivered the best surface roughness, combined with low porosity. Khanna et al found that the surface roughness was linearly related to the energy density in the process [10].…”
Section: Introductionmentioning
confidence: 99%